The use of social media in marketing musicians : focus on independent music management companies - Matikainen, Katriina (fi=Turun yliopisto|en=University of Turku|, 2018)
The digital era has brought great changes in the music industry and to the importance of the traditional set up of major labels and the independent labels. The digitalization of music and the rise of the social media has enabled individual musicians and various forms of independent music companies to succeed and grow their markets. The topic of this master thesis is the use of social media in marketing musicians focusing on the expert interviews from independent management companies. The purpose is to understand better the approach of the independent management companies on musicians and how the social media strategies are built to gain recognition and popularity. The research is divided into three sub-questions: which social media channels are used in promotion of musicians and what is their nature, how content can be used to get better engagement with fans and how social interaction can build partnerships to create new opportunities through social media? The theoretical background is built through the three sub-questions. Firstly, we are observing what kind of social media channels there are, how the right channel is chosen and how marketing objectives and positioning influence the choice of channel. Secondly, the different types of content are explored, what is the benefit of creating content and the different categorization of them. Thirdly, the effectuation theory is examined to study how the musicians can use social interaction to create new opportunities. The data is collected through semi-structured interviews from three Berlin based independent management companies who represent various number of musicians internationally. This study is a qualitative research using the grounded theory to build a better understanding on the topic, which doesn’t have a strong base from earlier research. The results of this study show that the independent management companies use the mainstream social media channels, which are Facebook, Instagram, Twitter and Youtube and they each have an individual nature to be approached with. The content created for musicians are music, photos, videos and playlists that can improve engagement though personalization, scheduling and optimization. The new business opportunities through social interaction are mainly build with other artists, brands and charities. The key is to understand what are the means the musicians can use and what risks and losses are they willing to take in pursuing these opportunities. Overall, the marketing of musicians using social media seems to have established practices from independent management company point of view, however the practices evolve mainly around the mainstream social media.